1990
DOI: 10.1007/bf00032166
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes of salt marsh communities by cattle grazing

Abstract: Over a period of 9 years a grazing experiment was carried out in the mainland salt marsh of the Leybucht (Niedersachsen) with three stocking rates, namely, 0.5 ha 1, 1 h a -~, and 2 cattle ha ~. These were also compared with an abandoned area. The results are based on sampling of the invertebrates in 1980, 1981, 1982, and 1988, and of the vegetation in 1980 and 1988. The rate of sedimentation is highest in the Puccinellia maritima-zone and decreases with the increase of stocking rates. The Elymus pycnanthus v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
110
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(122 citation statements)
references
References 3 publications
9
110
2
Order By: Relevance
“…Increasing food resources support population development for Symplecta stictica (Limoniidae) and also Nernotelus notatus (Stratiomyidae). Andresen et al (1990) demonstrated in their cattle-grazing study report that grazing changes community structure from dominance of herbivores to dominance of detritivores. The same is true here, except for collembolans, which do not react the same way under cattle grazing as they do under sheep grazing.…”
Section: Grazing Effectsmentioning
confidence: 99%
See 4 more Smart Citations
“…Increasing food resources support population development for Symplecta stictica (Limoniidae) and also Nernotelus notatus (Stratiomyidae). Andresen et al (1990) demonstrated in their cattle-grazing study report that grazing changes community structure from dominance of herbivores to dominance of detritivores. The same is true here, except for collembolans, which do not react the same way under cattle grazing as they do under sheep grazing.…”
Section: Grazing Effectsmentioning
confidence: 99%
“…In that study, a suction sampler with high efficiency only for epigaeic species was used, while a Kempsonextraction was used in this study with high efficiency for endofauna. Nevertheless, cattleand sheep-grazing appear to affect the fauna in the same way (Andresen et al, 1990;Grell, 1992), although they influence the abiotic environment differently.…”
Section: Grazing Effectsmentioning
confidence: 99%
See 3 more Smart Citations